Digital Trust and Checkout Choices: Empirical Evidence on Online Consumer Behavior in Asia: Online Consumer Behavior in Asia - Kowsar, Ali Mohammad; Roy, Shib Shankar; Latif, Wasib (Journal of Information Systems and Management (JISMA), 2025)
This paper considers the role of digital trust, perceived usefulness, social influence, and logistics reliability, as well as checkout option (cash-on-delivery and digital payment) in online consumer behavior among four Asian markets (Bangladesh, India, Indonesia and Vietnam). The information systems theory (TAM/UTAUT) and consumer trust literature guided the implementation of the study that provided cross-sectional survey (N = 2,412) and analyzed the findings through PLS-SEM with multi-group analysis. We discover that the strongest predictors of purchase intention are trust and logistics reliability whereas perceived usefulness is the major predictors of continuance intention. The choice of checkout has a dual nature: cash-on-delivery is perceived to reduce the perceived risk of payment and the trust-intention relationship in lower card-penetration samples but enhances the usefulness- continuance relationship in higher-adoption samples. The social influence has minor but influential effects, especially on the newer online shoppers. The invariance tests employed post-hoc demonstrates that these correlations hold up widely across the four markets, and there are significant differences in the degree of moderation of a checkout choice. We comment on the implication of information systems design and platform strategy with in particular information systems investments in transparent logistics, order tracking, and multi-rails payments. Some of the limitations are self-reported behavior and cross-sectional design. We find that there is a best fit between Asia and trust-first, rails-flexible architectures and suggest market sensitive nudges to shift to the digital-based without losing the perceived safety.